Outcome of Pregnant Patients with Cardiac Diseases Delivered in Tribhuvan University Teaching Hospital - Koirala, Megha; Shakya, Bigen Man; Parajuli, Basudev; Ghimire, Basanta; Katuwal, Neeta (Journal of Nepal Health Research Council, 2022)
Background: Pregnant women with cardiac disease pose a unique challenge to both the anaesthesiologists and obstetrician because of high morbidity affecting the maternal and fetal outcomes. Our research aims to provide an overview of pregnant women with heart disease coming for delivery in Tribhuvan University Teaching Hospital over one year, the occurrence of adverse maternal and neonatal outcome (mortality and morbidity) and correlation of certain maternal factors associated with adverse outcome.Methods: This is an observational cross-sectional study conducted in Tribhuvan University Teaching Hospital from 2075/11/01 to 2076/10/30 where data of pregnant women beyond 28 wks period of gestation with diagnosed cardiac disease was recorded from secondary sources.Results: The prevalence of pregnant women with cardiac disease presenting for delivery over one-year period was found out to be 120 (2.49%). Among them, almost 85 cases (71%) had valvular heart disease and 27 had mitral stenosis. The mortality was 2.5%. The complication rate among such patients was 30%, the patients requiring ICU admission was 20.7% and requiring mechanical ventilation was 6.7%. The neonatal mortality in such patients was 3.2% and 20.5% were premature, 27% had weight <2.5 kgs at birth and 10.7% required NICU admission. There was statistically significant association between history of prior cardiac event and NYHA with adverse maternal event with p value of <0.001. Conclusions: History of prior cardiac event and higher NYHA grading in a pregnant patient with cardiac disease are major determinants for adverse maternal outcome. Keywords: Maternal mortality; pregnancy complication.